When Heroes and Villains Are Victims: How Different Withdrawal Strategies Moderate the Depleting Effects of Customer Incivility on Frontline Employees. (August 2021) - Yue, Yumeng; Nguyen, Helena; Groth, Markus; Johnson, Anya; Frenkel, Stephen
Withdrawal from work by frontline employees (FLEs) is generally perceived by managers as counterproductive or anti-service behavior. However, there may be detrimental effects of continuing to provide a service, particularly after an FLE has experienced incivility. The possible beneficial effects of withdrawal on frontline service employees' well-being have rarely been investigated. In this article, we conducted two studies to examine the moderating role of on- and off-task withdrawal behaviors on the relationship between customer incivility and employees' emotional exhaustion. In Study 1, we examined parking officers' reactions to customer incivility. We found support for the role of off-task withdrawal as a resource-replenishing strategy, which mitigated the relationship between customer incivility and emotional exhaustion. In Study 2, we examined a sample of nurses in a large hospital to compare the replenishing potential of both on-task and off-task withdrawal strategies. We found that off-task withdrawal served a replenishing function, while on-task withdrawal aggravated nurses' feeling of emotional exhaustion as a result of customer incivility. These results highlight different resource implications, including recovery benefits of short-term withdrawal behaviors at work, and provide important theoretical and practical implications for the management of customer incivility and frontline service employees' well-being and performance.